SNARE Protein AoSec22 Orchestrates Mycelial Growth, Vacuole Assembly, Trap Formation, Stress Response, and Secondary Metabolism in Arthrobotrys oligospora - Yingmei Zhu; Duanxu Zhou; Na Bai; Qianqian Liu; Na Zhao; Jinkui Yang (Journal of Fungi, 2023)
Soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) facilitate intracellular vesicle trafficking and membrane fusion in eukaryotes and play a vital role in fungal growth, development, and pathogenicity. However, the functions of SNAREs are still largely unknown in nematode-trapping fungi. Arthrobotrys oligospora is a representative species of nematode-trapping fungi that can produce adhesive networks (traps) for nematode predation. In this study, we characterized AoSec22 in A. oligospora, a homolog of the yeast SNARE protein Sec22. Deletion of Aosec22 resulted in remarkable reductions in mycelial growth, the number of nuclei, conidia yield, and trap formation, especially for traps that failed to develop mature three-dimensional networks. Further, absence of Aosec22 impaired fatty acid utilization, autophagy, and stress tolerance; in addition, the vacuoles became small and fragmented in the hyphal cells of the ∆Aosec22 mutant, and large vacuoles failed to form. The reduced sporulation capacity correlated with the transcriptional repression of several sporulation-related genes, and the impaired accumulation of lipid droplets is in line with the transcriptional repression of several genes involved in fatty acid oxidation. Moreover, absence of Aosec22 remarkably impaired secondary metabolism, resulting in 4717 and 1230 compounds upregulated and downregulated in the ∆Aosec22 mutant, respectively. Collectively, our data highlighted that the SNARE protein AoSec22 plays a pleiotropic role in mycelial growth and development, vacuole assembly, lipid metabolism, stress response, and secondary metabolism; in particular, it is required for the proper development of traps in A. oligospora.